Qualities of the good language teacher as perceived by prospective teachers of English in the Arab World - Mohamed Ismail Abu-Rahmah (Sultan Qaboos University, 2008)
The purpose of this study was to identify the qualities of the good language teacher as perceived by student teachers of English in the Arab World. In Fall 2006, a questionnaire including 69 qualities of the good language teacher representing three dimensions (knowledge, teaching skills and personality) was developed, validated and administered to 273 prospective teachers of English in three countries of the Arab world (Egypt, Oman and Saudi Arabia). ANOVA test results indicated that there were statistically significant differences between the three groups as to the perception of theses qualities. There were statistically significant differences in the perception of the qualities between the male subjects and the female subjects in favour of females. It was concluded that (1) both the Saudi and Egyptian prospective teachers of English have similar views for the knowledge, and personality dimensions, whereas they have different views as to the teaching skills dimension, (2) both the Saudi students and the Omani students have different iiviews as to the qualities of the good language teacher, whereas the Egyptian students and the Omani students have the same views, and (3) the views of the female students as to the qualities of the good language teacher are different from the views of the male students. Accordingly, it was i recommended that two further studies are needed: (1) a l study to identify the qualities of the good language teacher using a large sample from different universities of the Arab World, and (2) an ethnographic study to investigate qualitatively and thoroughly what makes a good language teacher.